Hyperuniform disordered terahertz quantum cascade laser - Degl’Innocenti, R. (Sci Rep, 2016)
Laser cavities have been realized in various different photonic systems. One of the forefront research fields regards the investigation of the physics of amplifying random optical media. The random laser is a fascinating concept because, further to the fundamental research investigating light transport into complex media, it allows us to obtain non-conventional spectral distribution and angular beam emission patterns not achievable with conventional approaches. Even more intriguing is the possibility to engineer a priori the optical properties of a disordered distribution in an amplifying medium. We demonstrate here the realization of a terahertz quantum cascade laser in an isotropic hyperuniform disordered distribution exhibiting unique features, such as the presence of a photonic band gap, low threshold current density, unconventional angular emission and optical bistability.